An Iterative Algorithm for a Hierarchical Problem - Yonghong Yao; Yeol Je Cho; Pei-Xia Yang (Journal of Applied Mathematics)
A general hierarchical problem has been considered, and an explicit algorithm has been presented for solving this hierarchical problem. Also, it is shown that the suggested algorithm converges strongly to a solution of the hierarchical problem.